5PSQ-137 Adequacy of diagnosis and treatment of pharyngotonsillitis. (14th March 2021) - Salom, C; Bladé, J; Campabadal, C; Bejarano, F; Torrente, C; Piqueras, M; Marco, N; Castillo, L; Roch, MÁ; Sanjuan, A; Canadell, L
Abstract : Background and importance: Acute pharyngotonsillitis is the most prevalent infectious disease in primary healthcare, with inadequate prescription of antibiotics without diagnostic evidence through the application of the Centor criteria and the rapid antigen detection test for group A β-haemolytic Streptococcus . Aim and objectives: To evaluate in our territory the degree of adequacy of: (1) the diagnostic procedures for pharyngotonsillitis and (2) antibiotic treatment. Material and methods: A retrospective observational study was conducted in patients diagnosed with pharyngotonsillitis during 2019 in 20 primary healthcare centres. Demographic variables (age and sex), Centor criteria, rapid antigen test and antibiotic prescriptions were collected. Results: 5283 patients were included, aged 9 (6–13) years, and 2759 (52.2%) were women. Of 1062 (20.1%) adult patients, 234 (22%) did not have a record of the Centor score, and 420 (39.5%) with a Centor score ≥2 did not undergo an antigen test. Antibiotic treatment was given to 76 (7.2%) patients without registration of the Centor score or test, to 53 (5%) with a Centor score <2 and no test, and to 49 (4.6%) with a negative test. In contrast, 4 (0.4%) patients with a Centor score of ≥2 and a positive test did not receive an antibiotic. Of 4221 (79.9%) paediatric patients, 295 (7%) did not have a record of the Centor score, and 1492 (28.2%) with a Centor score ≥2 did not undergo a test. Antibiotic treatment was given to 97 (2.3%) patients without registration of the Centor score or test, to 53 (1.3%) with a Centor score of <2 and no test, and to 213 (5.1%) with a negative test. In contrast, 84 (2%) patients with a Centor score of ≥2 and a positive test did not receive an antibiotic. Conclusion and relevance: The pharyngotonsillitis diagnostic workup (application of the Centor criteria and rapid antigen test) was far from optimal, especially in the adult population. Accordingly, there was a moderately inappropriate prescription of antibiotics, although less in the paediatric population. Optimising the use of antibiotics in pharyngotonsillitis treatment requires maintenance of the dissemination of recommendations and advice. References and/or acknowledgements: Conflict of interest: No conflict of interest